Conducting polymer based hybrid nano-composites for enhanced corrosion protective coatings - Patil, R. C.; Radhakrishnan, S. (Progress in Organic Coatings, 2006)
Hybrid composite coatings containing zinc oxide (ZnO) and polyaniline (PANI) as nano-additives dispersions were prepared with poly(vinyl acetate) (PVAc) as the major matrix. The steel plates dip-coated with these formulations were tested for corrosion protection by immersion in saline water over long periods. The Tafel plots for the determination of open circuit potential (OCP) and corrosion current (I-corr) were recorded. The coatings containing both ZnO and PANI showed improved corrosion resistance as compared to the single component coating. The I-corr values of PVAc-ZnO-PANI are found to be two-order magnitude lower than that of PVAc and PVAc-ZnO coatings. The results are explained on the basis of enhancement in barrier properties due to nano-particulate additives in PVAc-ZnO-PANI film together with the redox behaviour of PANI and protective oxide layer formation near the substrate. (C) 2006 Elsevier B.V All rights reserved.
Keywords: Coatings; corrosion; nano-additives; polyaniline; ZnO

Correlation between mobility enhancement and conformational change in polyaniline and its derivatives: polaron lattice formation - Harima, Yutaka; Ogawa, Fumiyuki; Patil, Rahul; Jiang, Xiaoqing (Electrochimica Acta, 2007)
Conformational changes in polyaniline, poly(methyl aniline), and poly(methoxyaniline) are studied in perchloric acid and acetonitrile by means of an in situ reflection technique with oxidation level as a parameter. Stretching of polymer chains leading to enhancement of specular reflection at the polymer-coated electrodes is found to be well correlated with the increase in carrier mobility. The concomitant change in mobility and chain conformation observed with the polyaniline family is explained in terms of the formation of polaron lattice at increased oxidation levels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Conformation; polyaniline; reflection; scattering : mobility

New technique to study kinetics of chain conformation in polyaniline films - Harima, Yutaka; Kishimoto, Kazuya; Ogawa, Fumiyuki; Jiang, Xiaoqing; Patil, Rahul (Polymer Journal, 2007)
Keywords: Conformation; kinetics; laser; polyaniline; reflection

Synthesis, characterization and actuation behavior of polyaniline-coated electroactive paper actuators - Kim, Jaehwan; Yun, Sung-Ryul; Deshpande, S. D. (Polymer International, 2007)
This investigation deals with the synthesis, characterization and actuation behavior of conductive polyaniline-coated electroactive paper actuators. The actuator is made by electrochemical deposition of conductive polyaniline on a cellulose paper. The aim of the investigation was to improve the bending displacement of electroactive paper actuators. The displacement outputs of the actuators show that a trilayer is better than a bilayer configuration. The nature of the dopant ion used in the electro-generation affects the performance. A change in humidity plays a vital role in actuation performance of the actuators. Comparing the performance of electroactive paper actuators with and without a conductive polyaniline coating, the coating improves the displacement output threefold. Finally, the actuation principle mechanism is addressed. (C) 2007 Society of Chemical Industry.
Keywords: bending actuator; conducting polymer; electroactive polymer (EAP); polyaniline

Epoxy powder coatings containing polyaniline for enhanced corrosion protection - Radhakrishnan, S.; Sonawane, Narendra; Siju, C. R. (Progress in Organic Coatings, 2009)
Incorporation of polyaniline (PANI) in epoxy type powder coating formulations has not been attempted earlier. Using specific grade of PANI with low doping, it can be incorporated in epoxy powder coating formulations by twin screw extrusion process. The powder formulations were deposited on steel substrates by electrostatic spray coating at -60 W and baked at 140 degrees C for 20 min. These were extensively tested for corrosion resistance by exposure to hot saline conditions followed by electrochemical impedance spectroscopy and also salt spray testing. PANI incorporated coatings showed no deterioration even after 1400 h of hot (65 degrees C) saline treatment. The coatings intentionally scratched also exhibited self healing property and there was no rust formation even after prolonged exposure to hot saline conditions. These results could be explained on the basis of additional crosslinking due to PANI, as confirmed by DSC results, which gave rise to improved barrier property and self healing was associated with the scavenging of ions by PANI which prevented corrosion of the underlying substrate. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Corrosion resistance; Epoxy; polyaniline; Powder coating

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline

Polyaniline modified electrodes for detection of dyes - Mahanta, Debajyoti; Munichandraiah, N.; Radhakrishnan, S.; Madras, Giridhar; Patil, Satish (Synthetic Metals, 2011)
Polyaniline (PANI) is one of the most extensively used conjugated polymers in the design of electrochemical sensors. In this study, we report electrochemical dye detection based on PANI for the adsorption of both anionic and cationic dyes from solution. The inherent property of PANI to adsorb dyes has been explored for the development of electrochemical detection of dye in solution. The PANI film was grown on electrode via electrochemical polymerization. The as grown PANI film could easily adsorb the dye in the electrolyte solution and form an insulating layer on the PANI coated electrode. As a result, the current intensity of the PANI film was significantly altered. Furthermore, PANI coated stainless steel (SS) electrodes show a change in the current intensity of Fe(2+)/Fe(3+) redox peaks due to the addition of dye in electrolyte solution. PANI films coated on both Pt electrodes and non-expensive SS electrodes showed the concentration of dye adsorbed is directly proportional to the current intensity or potential shift and thus can be used for the quantitative detection of textile dyes at very low concentrations. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electrochemical sensor; Emeraldine base; Emeraldine salt; polyaniline

Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

3D polyaniline porous layer anchored pillared graphene sheets: enhanced interface joined with high conductivity for better charge storage applications - Sekar, Pandiaraj; Anothumakkool, Bihag; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Here, we report synthesis of a 3-dimensional (3D) porous polyaniline (PANI) anchored on pillared graphene (G-PANI-PA) as an efficient charge storage material for supercapacitor applications. Benzoic acid (BA) anchored graphene, having spatially separated graphene layers (G-Bz-COOH), was used as a structure controlling support whereas 3D PANI growth has been achieved by a simple chemical oxidation of aniline in the presence of phytic acid (PA). The BA groups on G-Bz-COOH play a critical role in preventing the restacking of graphene to achieve a high surface area of 472 m(2)/g compared to reduced graphene oxide (RGO, 290 m(2)/g). The carboxylic acid (-COOH) group controls the rate of polymerization to achieve a compact polymer structure with micropores whereas the chelating nature of PA plays a crucial role to achieve the 3D growth pattern of PANI. This type of controlled interplay helps G-PANI-PA to achieve a high conductivity of 3.74 S/cm all the while maintaining a high surface area of 330 m(2)/g compared to PANI-PA (0.4 S/cm and 60 m(2)/g). G-PANI-PA thus conceives the characteristics required for facile charge mobility during fast charge-discharge cycles, which results in a high specific capacitance of 652 F/g for the composite. Owing to the high surface area along with high conductivity, G-PANI-PA displays a stable specific capacitance of 547 F/g even with a high mass loading of 3 mg/cm(2), an enhanced areal capacitance of 1.52 F/cm(2), and a volumetric capacitance of 122 F/cm(3). The reduced charge-transfer resistance (RCT) of 0.67 O displayed by G-PANI-PA compared to pure PANI (0.79 O) stands out as valid evidence of the improved charge mobility achieved by the system by growing the 3D PANI layer along the spatially separated layers of the graphene sheets. The low RCT helps the system to display capacitance retention as high as 65% even under a high current dragging condition of 10 A/g. High charge/discharge rates and good cycling stability are the other highlights of the supercapacitor system derived from this composite material.
Keywords: durability; ionic accessibility; phytic acid; pillaring; polyaniline; restacking

Facile synthesis and electrochemical evaluation of PANI/CNT/MoS2 ternary composite as an electrode material for high performance supercapacitor - Thakur, A.K.; Deshmukh, A. B.; Choudhary, R. B.; Karbhal, I.; Majumder, M.; Shelke, M.V. (Materials Science and Engineering B: Solid-State Materials for Advanced Technology, 2017)
Synthesis of a novel ternary composite consisting of polyaniline (PANI), functionalized multi-walled carbon nanotubes (CNTs) and molybdenum disulfide (MoS2), via an in-situ polymerization method is reported. Detailed structural and electrochemical characterization shows that incorporation of a small amount of MoS2 in PANI/CNT composite tends to eliminate agglomeration problem of CNT. The PANI/CNT/MoS2 ternary composite reaches a specific capacitance of 350 F/g at the current density 1 A/g corresponding to a 5% MoS2 content. This ternary composite shows good cycling stability even at a higher energy density of 10 A/g. Further, PANI/CNT/MoS2 composite electrode shows higher energy density (7.77 Wh/kg) and power density (2140 W/kg) as compared to PANI/CNT composite without MoS2.
Keywords: MoS2; polyaniline; supercapacitor; Ternary Composite

Realizing high capacitance and rate capability in polyaniline by enhancing the electrochemical surface area through induction of superhydrophilicity - Soni, Roby; Kashyap, Varchaswal; Nagaraju, Divya; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2018)
Polyaniline (PANI) as a pseudocapacitive material has very high theoretical capacitance of 2000 F g(-1). However, its practical capacitance has been limited by low electrochemical surface area (ESA) and unfavorable wettability toward aqueous electrolytes. This work deals with a strategy wherein the high ESA of PANI has been achieved by the induction of superhydrophilicity together with the alignment of PANI exclusively on the surface of carbon fibers as a thin layer to form a hybrid assembly. Superhydrophilicity is induced by electrochemical functionalization of the Toray carbon paper, which further induces superhydrophilicity to the electrodeposited PANI layer on the paper, thereby ensuring a high electrode-electrolyte interface. The Toray paper is electrochemically functionalized by the anodization method, which generates a highly active electrochemical surface as well as greater wettability (superhydrophilic) of the carbon fibers. Because of the strong interaction of anilinium chloride with the hydrophilic carbon surface, PANI is polymerized exclusively over the surface of the fibers without any appreciable aggregation or agglomeration of the polymer. The PANI-Toray paper assembly in the solid-state prototype supercapacitor can provide a high gravimetric capacitance of 1335 F g(-1) as well as a high areal capacitance of 1.3 F cm(-2) at a current density of 10 A g(-1). The device also exhibits high rate capability, delivering 1217 F g(-1) at a current density of 50 A g(-1) and a high energy density of 30 W h kg(-1) at a power density of 2 kW kg(-1).
Keywords: electrochemical active sulfate area; electrochemical functionalization; electropolymerization; polyaniline; supercapacitor; superhydrophilic

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors

PANI-grafted boron, nitrogen co-doped carbon fiber: An outstanding, high-performance supercapacitor electrode - Nayan, Rajiv; Sinha, Shubhra; Dixit, Vaibhav; Satnami, Manmohan L.; Ghosh, Kallol K.; Pervez, Shamsh; Deb, Manas Kanti; Shrivas, Kamlesh; Rai, Manish K.; Yenchalwar, Sandeep G.; Wasnik, Kundan; Jadkar, Sandesh R.; et al. (JOURNAL OF ENERGY STORAGE, 2024)
Keywords: Composite; polyaniline; Solid-state supercapacitor